Pengaruh Layanan Konseling Kelompok dengan Pendekatan Behavior Terhadap Perilaku Bullying Siswa Kelas VIII di SMP N 1 Demak - Khafidhiyah, Khusnul; Fitriana, Siti; Venty, Venty (Jurnal Psikoedukasia, 2023)
This study aims to determine the effect of group counseling services with a behavior approach on bullying behavior of class VIII students at Demak 1 Public Middle School. This type of research is quantitative. The research method used in this study was a pre-experimental design with a one group pretest posttest research design. The population of this research is the research population of 313 students. The sample taken was class VIII B, which consisted of 32 students using purposive sampling technique. The data in this study were obtained through a psychological scale. Abnormal data using the Wilcoxon test is significant (2-tailed) of 0.005. From the basis of the decision in the calculation of the Wilcoxon test, the sig. 0.005 <0.05 which means that the proposed hypothesis is "accepted". There is a difference between the results of bullying behavior after being given treatment in the form of group counseling services using behavioral contract techniques at the pretest and posttest, so that it can be said that "there is an influence of group counseling services with a behavior approach on bullying behavior in class VIII students of SMP Negeri 1 Demak". Based on the results of this study, the suggestion that can be conveyed is that group counseling services with a behavior approach can be used by counseling teachers to reduce student bullying behavior. Keywords: Group Counseling, Behavior, Bullying Behavior